BacPROTACs targeting Clp protease: a promising strategy for anti-mycobacterial drug discovery - Bonjorno, Andressa Francielli; Pavan, Aline Renata; Fernandes, Guilherme F. S.; Scarim, Cauê Benito; Castagnolo, Daniele; Dos Santos, Jean Leandro (Frontiers in Chemistry, 2024)
Tuberculosis (TB) has claimed more lives over the course of two millennia than any other infectious disease worldwide. In 2021, the World Health Organization (WHO) estimated that 10.6 million people were diagnosed with TB, resulting in the deaths of 1.4 million HIV-negative individuals. The emergence of multidrug-resistant TB (MDR-TB), defined as resistance to at least rifampicin (RIF) and isoniazid (INH), and extensively drug-resistant TB (XDR-TB), poses the primary challenge to overcome in the coming years.We have recently conducted an extensive analysis of investments and research endeavours in the field, with the overarching objective of achieving the established milestone of TB eradication by the year 2030. Over the past several years, there has been notable progress in advancing a multitude of promising compounds, each possessing distinct mechanisms of action, into clinical phases of development. However, it is worth noting that strains of mycobacteria resistant to current antitubercular drugs have already emerged for some of these compounds The exploration of the innovative Proteolytic Target Chimeras (PROTACs) protein degradation approach has emerged as a viable avenue for the discovery of novel antimicrobials. While the ubiquitin system is exclusive to eukaryotic cells, certain bacteria employ a similar degradation system that relies on the recognition of phosphorylated arginine residues (pArg) by the ClpC:ClpP (ClpCP) protease, thereby leading to protein degradation. In this opinion article, we have described and analized the advances in the use of PROTACs that leverage bacterial proteolytic machinery (BacPROTACs) to design new antitubercular agents.